Public management and policy networks. Foundations of a network approach to governance: with the introduction of Bob Jessop - Klijn, Erik-Hans; Koppenjan, Joop F.M. (Journal of Public Governance, 2012)
In this article we address the elaboration of the central concepts of a theory of networks and of network management. We suggest that the network approach builds on several theoretical traditions. After this we clarify the theoretical concepts and axioms of the policy network approach and argue that this framework has important explanatory power both on the level of strategic interaction processes as well as on the level of institutional relations. We argue that government’s special resources and its unique legitimacy as representative of the common interest make it the outstanding candidate for fulfi lling the role of network manager, a role which means arranging and facilitating interaction processes within networks in such a way that problems of under or non representation are properly addressed and interests are articulated and dealt with in an open, transparent and balanced manner.